2019
DOI: 10.1038/s41438-019-0209-4
|View full text |Cite
|
Sign up to set email alerts
|

Selection footprints reflect genomic changes associated with breeding efforts in 56 cucumber inbred lines

Abstract: Cucumber selective breeding over recent decades has dramatically increased productivity and quality, but the genomic characterizations and changes associated with this breeding history remain unclear. Here, we analyzed the genome resequencing data of 56 artificially selected cucumber inbred lines that exhibit various phenotypes to detect trait-associated sequence variations that reflect breeding improvement. We found that the 56 cucumber lines could be assigned to group 1 and group 2, and the two groups formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…The two parental lines, 2073-1 and 2073-2, are a pair of NILs at the D locus that bear dull and glossy fruits, respectively [ 17 ]. For convenience, based on the days before or after pollination we divided fruit development in the lines into six stages: stage 1 to stage 6.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two parental lines, 2073-1 and 2073-2, are a pair of NILs at the D locus that bear dull and glossy fruits, respectively [ 17 ]. For convenience, based on the days before or after pollination we divided fruit development in the lines into six stages: stage 1 to stage 6.…”
Section: Resultsmentioning
confidence: 99%
“…The cucumber lines 2073-1 (P 1 , dull fruit) and 2073-2 (P 2 , glossy fruit) used in this study are a pair of near-isogenic lines (NILs) at the D locus and were isolated from a high-generation inbred population [ 17 ]. More concretely, 2073-1 is an inbred line selected from the F 9 population whose female and male parent are DeltaStar (P 1 , a commercial variety of the Rijk Zwaan company) and 3461 (P 2 , a high-generation inbred line developed by our laboratory), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We found that the CDSs of CsSBS1 were identical in L‐SB and all 25 large spine base cucumber, while the 4895 bp fragment deletion was detected in all 25 cucumber lines with small spine bases, suggesting that the CsSBS1 gene was lost in these small spine base cucumber accessions (Table S3). In addition, we also performed a sequence variation analysis within an 18‐kb region flanking the CsSBS1 locus in 56 resequencing cucumber lines (Liu et al ., 2019). This further confirmed that the absence of the CsSBS1 gene was pervasive in 26 different cucumber lines with small spine bases, while CsSBS1 existed in all large spine bases cucumber lines (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, all the current assemblies do likely contain the majority of the coding regions of the cucumber genome, facilitating the development of molecular markers and linkage maps to help with genetic studies and molecular breeding. During the past decade, several high-density genetic maps of cucumber have been developed (Ren et al, 2009;Cavagnaro et al, 2010;Yang et al, 2013;Rubinstein et al, 2015;Zhou et al, 2015), and more than 300 cucumber lines re-sequenced (Qi et al, 2013;Bo et al, 2016;Liu et al, 2019a). Further, over 1,200 cucumber accessions in the USDA national germplasm collection have been genotyped using GBS technology, resulting in the public availability of hundreds of thousands of molecular markers (Wang et al, 2018a).…”
Section: A Genetic and Genomic Resourcesmentioning
confidence: 99%